1997
DOI: 10.1116/1.580859
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of metal–insulator–semiconductor structures with silicon nitride dielectrics deposited by low temperature plasma enhanced chemical vapor deposition distributed electron cyclotron resonance

Abstract: Articles you may be interested inLow-temperature electron cyclotron resonance plasma-enhanced chemical-vapor deposition silicon dioxide as gate insulator for polycrystalline silicon thin-film transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Due to lower energy barrier and higher density of hole traps, the hole injection and transport through silicon dangling bond are more favored than electron injection and transport in the silicon-rich nitride film. Similar phenomena were also found in other work [4,19,20].…”
Section: Charging Behavior Under DC Stresssupporting
confidence: 91%
“…Due to lower energy barrier and higher density of hole traps, the hole injection and transport through silicon dangling bond are more favored than electron injection and transport in the silicon-rich nitride film. Similar phenomena were also found in other work [4,19,20].…”
Section: Charging Behavior Under DC Stresssupporting
confidence: 91%
“…The electrical resistivity of silicon nitride is governed by the formation of electrically conductive path. It was reported that the electrical resistivity of typical Y–Si–A1 oxynitride glasses was lower than 10 11 Ω cm, while resistivity of 10 16 Ω cm was reported for Si 3 N 4 on n‐type silicon . In those oxide additives doped silicon nitride, the liquid phases remain as amorphous and/or crystalline oxynitride glasses at the multigrain junction and grain boundary films after cooling, so the electrical resistivity was deteriorated by the lower resistivity oxynitride glasses, especially the grain boundary films path.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the electrical resistivity of typical Y-Si-A1 oxynitride glasses was lower than 10 11 Ω cm, while resistivity of 10 16 Ω cm was reported for Si 3 N 4 on n-type silicon. 54,55 In those oxide additives doped silicon nitride, the liquid phases remain as amorphous and/or crystalline oxynitride glasses at the multigrain junction and grain boundary films after cooling, so the electrical resistivity was deteriorated by the lower resistivity oxynitride glasses, especially the grain boundary films path. In this work, non-oxide additive was applied, the volume fraction of the glassy phase was reduced, so deterioration from oxynitride glasses was weakened.…”
Section: Mechanical Properties and Electrical Resistivitymentioning
confidence: 99%
“…Dielectric films of silicon nitride ceramics play an integral role in nearly every semiconductor device and integrated circuit. Among this Silicon Nitride ceramic is used as a gate dielectric layer, diffusion barrier and optoelectronic-integrated circuits [3][4][5]. Low-density porous silicon nitride [6][7][8][9][10][11][12] ceramic is an important material with properties including low dielectric constant (   = 2.5 to 8, tan δ ≤ 3 × 10 -3 ), good mechanical, high resistance to rain erosion and sand erosion.…”
Section: Introductionmentioning
confidence: 99%